Inıtıal Needs Analysıs Development Of Image Letter Card Medıa Based Dıgıtal Barcode For Elementary School - Devi Ristyana Puji Lestari; Nurul Istiq’faroh; Budi Purwoko (Jurnal Elementaria Edukasia, 2025)
This study aims to analyze the initial needs for media development as an effort to improve the reading skills of elementary school students. The method used in the research is qualitative descriptive with research instruments in the form of observation, questionnaires, and interviews. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. Based on the initial needs assessment data analysis, it is known that students' reading skills are still low. The difficulties in early reading include some students not recognizing letters, students being unable to distinguish letters that look similar, students being unable to blend syllables, and some students stuttering while reading. Most students admitted to being more interested in the additional media of illustrated letter cards based on digital barcodes, with 83% expressing this preference. Furthermore, this study can be used as an initial needs analysis for the development of media in the form of illustrated letter cards based on digital barcodes that are suitable for training reading skills.